2022
DOI: 10.33545/26646064.2022.v4.i1a.45
|View full text |Cite
|
Sign up to set email alerts
|

Eucalypt in the Tunisian arid region: Diversity and valorization for honey production

Abstract: Submission of an original paper with copyright agreement and authorship responsibility.I (corresponding author) certify that I have participated sufficiently in the conception and design of this work and the analysis of the data (wherever applicable), as well as the writing of the manuscript, to take public responsibility for it. I believe the manuscript represents valid work. I have reviewed the final version of the manuscript and approve it for publication. Neither has the manuscript nor one with substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Australian Native Plants Nursery (2015) mentioned that E. torquata is tolerant of extended dry periods (El-juhany et al, 2008), also, in Saudi Arabia it was classified among the high tolerating species to drought (El-juhany and Al Al-Shaikh, 2015). In the Mediterranean arid regions, E. torquata showed a high tolerance level and flower abundance also in the southern provinces of North Africa (Chemlali et al, 2022). Mechanisms employed for drought resilience of E. torquata were investigated by Souden et al (2020) which reported physiological and biochemical responses of this species subjecting to a dehydration period followed by rehydration.…”
Section: Responses To Droughtmentioning
confidence: 99%
See 3 more Smart Citations
“…Australian Native Plants Nursery (2015) mentioned that E. torquata is tolerant of extended dry periods (El-juhany et al, 2008), also, in Saudi Arabia it was classified among the high tolerating species to drought (El-juhany and Al Al-Shaikh, 2015). In the Mediterranean arid regions, E. torquata showed a high tolerance level and flower abundance also in the southern provinces of North Africa (Chemlali et al, 2022). Mechanisms employed for drought resilience of E. torquata were investigated by Souden et al (2020) which reported physiological and biochemical responses of this species subjecting to a dehydration period followed by rehydration.…”
Section: Responses To Droughtmentioning
confidence: 99%
“…The genus Eucalyptus comprises more than 800 species and hybrids, which includes 2 shrubs and flowering trees. It is the most valuable genus and it is found in almost all parts of the world due to human introduction (Chemlali et al, 2022). It has been broadly cultivated in many countries to utilize as wood for a diverse range of products and grow across a large range of climatic environments and soil types.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
See 2 more Smart Citations